Unlocking climate finance and investment in Zimbabwe: An analysis of the forestry sector performance - Jakarasi, Veronica (Graduate School of Business (GSB), 2023)
Globally, forest and tree resources directly support about 1.6 billion people's livelihoods. The forestry business provides both informal and official employment opportunities, generating approximately $244 billion in global forest product trade. The African region is more vulnerable to climate change due to constraint financial, institutional and technological capabilities. Given the importance of the forestry sector, there has been a rapid increase in initiatives to mitigate overexploitation of forests and address the developmental challenge of climate change such as the 2021 Glasgow Forestry Declaration and the 2015 Paris Climate Agreement. These are now on many countries' domestic development agendas. Therefore, the study explores the relationship, between climate financing and performance of the forestry sector in Zimbabwe covering period 2010 to 2018. To investigate the status of climate financing in the forestry sector in Zimbabwe, the mixed method approach was employed since it gives detailed, contextualized insights of qualitative data and generalizable, externally valid insights of quantitative data. The qualitative technique was employed to reinforce the quantitative technique in giving deep insight on the importance of climate financing in the forestry sector from the different experts in the field of climate finance and the forestry sector. According to the findings of the study, it can be noted that climate finance plays an important role in forestry sector performance as measured by Return on Assets and Return on Equity for the three companies evaluated. The results further highlighted that minimal funds are being channelled to the forestry sector despite their far greater demands as also demonstrated by the responses from the questionnaire and the interview guide. The results suggest that the Government of Zimbabwe, companies and all the organisations in the forestry sector must invest in climate financing to improve the performance of the sector. The unlocking of climate finance in the sector will assist in mitigating the constraints encountered by the sector because of climate change, such as increasing pests and diseases through purchasing chemicals for tree treatment and by assisting communities in dealing with droughts, as they rely heavily on forests during droughts. Additionally, the study found that capacity building for developing high-impact, quality and bankable projects; data availability; and co-financing were critical enablers for securing climate finance. The study recommended that governments should play a much larger role in raising public awareness on the critical roles played by forestry and the potential positive outcomes they have if they receive unhindered financial provision